Trade unions and the labour market - Mayhew, Ken. (Oxford : M. Robertson, 1983)
It is a study of unions and their impact on the economy. It is also concerned with industrial relations and with the history of the union movement. It places particular emphasis on government policy. The book will prove invaluable to second and third year undergraduates, and first year graduates, studying economics, industry and management.
Includes bibliographical references and index.
rpm 04/05/2018
Loans
Keywords: Labor unions; Labor economics; Labor supply